Small RNA-big impact: exosomal miRNAs in mitochondrial dysfunction in various diseases - Xiaqing Li; Yi Han; Yu Meng; Lianghong Yin (RNA Biology)
Mitochondria are multitasking organelles involved in maintaining the cell homoeostasis. Beyond its well-established role in cellular bioenergetics, mitochondria also function as signal organelles to propagate various cellular outcomes. However, mitochondria have a self-destructive arsenal of factors driving the development of diseases caused by mitochondrial dysfunction. Extracellular vesicles (EVs), a heterogeneous group of membranous nano-sized vesicles, are present in a variety of bodily fluids. EVs serve as mediators for intercellular interaction. Exosomes are a class of small EVs (30–100 nm) released by most cells. Exosomes carry various cargo including microRNAs (miRNAs), a class of short noncoding RNAs. Recent studies have closely associated exosomal miRNAs with various human diseases, including diseases caused by mitochondrial dysfunction, which are a group of complex multifactorial diseases and have not been comprehensively described. In this review, we first briefly introduce the characteristics of EVs. Then, we focus on possible mechanisms regarding exosome-mitochondria interaction through integrating signalling networks. Moreover, we summarize recent advances in the knowledge of the role of exosomal miRNAs in various diseases, describing how mitochondria are changed in disease status. Finally, we propose future research directions to provide a novel therapeutic strategy that could slow the disease progress mediated by mitochondrial dysfunction.